Family Approach Model in Affecting Cognitive and Psychomotor of Women of Reproductive Age to Use Long-term Contraceptive Method - Kusumawati, Widya; Rosidah, Lely Khulafa’ur (Journal of Maternal and Child Health, 2020)
Background: Family planning and birtth con